ЕНЕРГЕТИЧНІ ХАРАКТЕРИСТИКИ ЕЛЕКТРОМАГНІТНОГО ВІБРАЦІЙНОГО ПРИВОДА ЗА ІМПУЛЬСНОГО ЖИВЛЕННЯ ОБМОТОК ВІБРАТОРА - Черно, О.О.; Гуров, А.П.; Іванов, А.В. (Інститут електродинаміки НАН України, Київ, 2023)
Vibrating equipment provides various technological processes, such as transportation, separation, compaction of mixtures. The electromagnetic drive is usually used in vibrating conveyors, feeders and other devices where vibration parameters are automatically controlled. Increasing the energy efficiency of such devices is an important task. The paper examines the influence of the power supply voltage on the energy characteristics of the electromagnetic vibration drive and determines the most effective voltage form. To do this, an analysis of factors affecting the efficiency of the drive was carried out. It was found that one of the factors is the time interval between the maximum current and the minimum value of the air gap, and increasing the efficiency is possible by reducing this interval by forming bipolar rectangular voltage pulses with maximum amplitude, which create narrow sharp pulses of the vibrator coil current. As a result of the numerical modeling of the processes in the drive, it was found that with increasing power, current pulses cause short-term deep saturation of steel, which leads to increased losses and reduced efficiency. Therefore, a zero voltage interval was added between the positive and negative voltage pulses, which limits the peak current values. The simulation of the processes in the vibration drive with the voltage supply of the proposed form was carried out, its energy characteristics were calculated: the dependence of the efficiency on the frequency at different load values, the dependence of the maximum values ​​of the efficiency on the power. It was established that the use of pulsed power supply makes it possible to increase the efficiency of the drive up to 80% in the power range from 0.25 of the nominal value to the nominal one, which is on average 10% more compared to sinusoidal voltage. The dependences of frequency and zero voltage interval optimal values (according to the criterion of maximum efficiency) on power, which can be used in automatic control of the drive, have been obtained. References 10, figures 9, tables. 2.